Pembrolizumab plus chemotherapy versus chemotherapy alone in patients with advanced non–small cell lung cancer without tumor PD‐L1 expression: A pooled analysis of 3 randomized controlled trials. Issue 22 (11th September 2020) - Borghaei, Hossein; Langer, Corey J.; Paz‐Ares, Luis; Rodríguez‐Abreu, Delvys; Halmos, Balazs; Garassino, Marina C.; Houghton, Baerin; Kurata, Takayasu; Cheng, Ying; Lin, Jianxin; Pietanza, M. Catherine; Piperdi, Bilal; et al.
Abstract : Background: Pembrolizumab plus platinum‐based chemotherapy has demonstrated improved clinical outcomes over chemotherapy alone in patients with previously untreated advanced/metastatic non–small cell lung cancer (NSCLC), regardless of tumor programmed death ligand 1 (PD‐L1) expression. This study pooled data from 3 randomized controlled trials to evaluate outcomes with pembrolizumab plus chemotherapy versus chemotherapy alone in patients with advanced/metastatic NSCLC negative for PD‐L1 (ie, a tumor proportion score < 1%). Methods: Individual patient data were pooled from KEYNOTE‐021 cohort G (nonsquamous; NCT02039674), KEYNOTE‐189 (nonsquamous; NCT02578680 and NCT03950674), and KEYNOTE‐407 (squamous; NCT02775435). Treatment comprised pembrolizumab plus chemotherapy (pemetrexed and platinum for nonsquamous histology and carboplatin and paclitaxel/nab‐paclitaxel for squamous histology) or chemotherapy alone. Responses were assessed according to Response Evaluation Criteria in Solid Tumors version 1.1 by blinded, independent, central review. No α was assigned to this descriptive, exploratory analysis. Results: Four hundred forty‐four of the 1328 patients (33.4%) who were enrolled across the 3 trials had PD‐L1‒negative tumors (256 on pembrolizumab plus chemotherapy [nonsquamous, n = 155; squamous, n = 94; other, n = 7] and 188 on chemotherapy alone [nonsquamous, n = 83; squamous, n = 99; other, n = 6]). The median time from randomization to the data cutoff was 28.0 months (range, 14.7‐55.4 months). Pembrolizumab plus chemotherapy improved overall survival (OS; hazard ratio [HR], 0.63; 95% CI, 0.50‐0.79) and progression‐free survival (HR, 0.68; 95% CI, 0.56‐0.83) over chemotherapy. Sixteen patients in the pembrolizumab plus chemotherapy arm completed 2 years of treatment; the objective response rate was 87.5% (95% CI, 61.7%‐98.4%), and the 3‐year OS rate was 100%. Adverse events (AEs) were experienced by 99.2% of the patients who received pembrolizumab plus chemotherapy and by 98.9% of the patients who received chemotherapy alone, with grade 3 or higher AEs occurring in 71.4% and 72.0%, respectively; immune‐mediated AEs and infusion reactions were experienced by 29.0% and 12.4%, respectively. Conclusions: Pembrolizumab plus chemotherapy demonstrated response and survival improvements with manageable safety in comparison with chemotherapy alone in PD‐L1‒negative advanced/metastatic NSCLC, and it is a standard‐of‐care first‐line therapy for patients with advanced NSCLC, regardless of PD‐L1 expression. Lay Summary: Some tumors produce a protein called programmed death ligand 1 (PD‐L1), which interacts with the body's immune system and prevents an immune response against cancer. Antibody therapies such as pembrolizumab block interactions between tumor PD‐L1 and the immune system and enable an immune response. Used alone, pembrolizumab provides benefit for patients with non–small cell lung cancer (NSCLC) tumors that produce PD‐L1. However, when it is combined with chemotherapy, which can stimulate anticancer immune responses, pembrolizumab provides a benefit, regardless of tumor PD‐L1 production. This article shows that among patients with NSCLC whose tumors produce no PD‐L1, outcomes are better with pembrolizumab plus chemotherapy in comparison with chemotherapy alone. Abstract : This pooled analysis of individual patient data from 3 randomized controlled trials showed a clinically meaningful benefit and a manageable safety profile with pembrolizumab plus platinum‐based chemotherapy versus chemotherapy alone in previously untreated advanced/metastatic non–small cell lung cancer (NSCLC) negative for programmed death ligand 1 (PD‐L1). Pembrolizumab plus platinum‐based chemotherapy is a standard‐of‐care first‐line therapy for patients with advanced squamous or nonsquamous NSCLC, including patients with PD‐L1–negative tumors.